New Data on the Subfamily Otitinae (Diptera, Ulidiidae) in the Fauna of Iran - Mohamadzade Namin, S.; Nozari, J.; Najarpoor, A. (Вестник зоологии, 2012)
As a result of studies on picture-wing flies of the subfamily Otitinae in 2008–2011, Ceroxys robusta (Loew), C. munda (Loew), Herina rivosecchii Merz, Melieria subapennina (Rondani) and Myennis octopunctata (Coquebert) are recorded for the first time from Iran, and H. rivosecchii is recorded for the first time from Asia. В результате изучения мух-лентокрылок подсемейства Otitinae в Иране в 2008—2011 гг., Ceroxys robusta (Loew), C. munda (Loew), Herina rivosecchii Merz, Melieria subapennina (Rondani) и Myennis octopunctata (Coquebert) отмечены впервые для фауны Ирана, а H. rivosecchii также впервые зарегистрирован в Азии.